Open wedge metatarsal osteotomy versus crescentic osteotomy to correct severe hallux valgus deformity – A prospective comparative study. Issue 1 (March 2016) - Wester, Jens Ulrik; Hamborg-Petersen, Ellen; Herold, Niels; Hansen, Palle Bo; Froekjaer, Johnny
Highlights: Prospective randomized trial comparing two groups. Open wedge osteotomy versus crescentic osteotomy. No significant difference in radiological correction. No significant difference in clinical outcome after 1 year (AOFAS score, VAS score). Abstract: Background: Different techniques of proximal osteotomies have been introduced to correct severe hallux valgus. The open wedge osteotomy is a newly introduced method for proximal osteotomy. The aim of this prospective randomized study was to compare the radiological and clinical results after operation for severe hallux valgus, comparing the open wedge osteotomy to the crescentic osteotomy which is our traditional treatment. Methods: Forty-five patients with severe hallux valgus (hallux valgus angle >35̊, and intermetatarsal angle >15̊) were included in this study. The treatment was proximal open wedge osteotomy and fixation with plate (Hemax), group 1, or operation with proximal crescentic osteotomy and fixation with a 3 mm cannulated screw, group 2. The mean age was 52 years (19–71). Forty-one females and four males were included. Clinical and radiological follow-ups were performed 4 and 12 months after the operation. Results: In group 1 the hallux valgus angle decreased from 39.0̊ to 24.1̊ after 4 months and 27.9̊ after 12 months. In group 2 the angle decreased from 38.3̊ to 21.4̊ after 4 months and 27.0̊ after 12 months. The intermetatarsal angle in group 1 was 19.0̊ preoperatively, 11.6̊ after 4 months and 12.6̊ after 12 months. In group 2 the mean intermetatarsal angle was 18.9̊ preoperatively, 12.0̊ after 4 months and 12.6̊ after 12 months. The AOFAS score improved from 59.3 to 81.5 in group 1 and from 61.8 to 84.8 in group 2 respectively measured 12 months postoperatively. The relative length of the 1 metatarsal compared to 2 metatarsal bone was 0.88 and 0.87 preoperatively and 0.88 and 0.86 for group 1 and 2 respectively measured after 12 months. Conclusion: Crescentic osteotomy and open wedge osteotomy improve AOFAS score and VAS scores on patients operated with severe hallux valgus. No significant difference was found in the two groups looking at the postoperative improvement of HVA and IMA measured 4 and 12 months postoperatively. The postoperative VAS score and AOFAS score were comparable for the two groups with no significant difference. An expected tendency to gain better length of the first metatarsal using the open wedge osteotomy compared to the crescentic osteotomy was not found. Even though the IMA and HVA reduction was only suboptimal the improvement in AOFAS score was comparable to other similar clinical trials.